Qualidade do solo em agroecossistemas da região semiárida do Estado do Rio Grande do Norte - Gondim, Joaquim Emanuel Fernandes (2018)
Researches aimed to soil quality assessment and the community of macroarthropods in agroecosystems in the Apodi Plateau RN are incipient. Therefore, the present study aimed to evaluate the soil quality and the community of macroarthropods in agroecosystems of the Moacir Lucena settlement, Apodi Plateau RN. Soil profile openings were carried out in the environments of Native Vegetation (Ferralsol), Agroecological (Acrisol), Short Cycle Cultivation (Cambissol) and Fruticulture (Ferralsol), where samples with deformed structure and not deformed in its horizons were collected. Interpolations were performed in the layers 0,00-0,05 0,05-0,15 and 0,15-0,25 m for physical analysis (soil granulometric, soil density, WAD, GMD and water retention) (pH, EC, TOC, macronutrients, BS, CEC, V, PTS and m) and biological (provid traps in each environment in the dry and rainy periods to monitor the macroarthropods community of soil). Multivariate statistics was performed for data analysis. Soil quality indexes were generated for the 0,00-0,25 m layer, using a methodology proposed by Karlen and Stott (1994). The physical attributes of coarse sand, fine sand and total sand were more sensitive in the distinction between the environments of Native Vegetation and Fruticulture (Ferralsol) as well as the chemical attributes such as total organic carbon, potential acidity and aluminum. The differentiation of the Agroecological Environment (Acrisol) was given in function of the variables clay and total porosity, besides the greater water retention in the layer of 0,15-0,25 m, and also regarding the chemical attributes of sodium and exchangeable sodium percentage. The Short Cycle Cultivation environment (Cambissol) was discriminated by the average diameter and higher water retention for the three depths. Regarding the chemical attributes, stood out the calcium, magnesium, sum of base content, cation exchange capacity and hydrogen ion potential. For the soil quality, the Short Cycle and Agroecological Cultivation Environments presented the best indexes. The structure of the edaphic macroarthropod community in the Apodi Plateau RN region was influenced by seasonal variations, agricultural uses and physical and chemical attributes of the soil. In general, greater frequency of occurrence, dry biomass, richness and ecological indexes at the level of order are maintained in the Native and Agroecological Vegetation environments in the rainy season in detriment of to the other environments. The physical attributes related to soil structure (MWD and Tp) and the chemical attributes pH, Ca, Mg and CEC influenced the occurrence of the functional group litter transformes (Coleoptera) in the Short Cycle Cultivation Environment (SCC - Cambissol). The predatory functional group (Araneae) was influenced by the total organic carbon and soil density in the Fruticulture Environment (EF - Ferralsol).